Eliminação segura de arquivos em memória não-volátil - Weber, Julia Silva (2017)
The advent of the Internet of Things (IoT) and the popularization of mobile devices with non-volatile memory brings new challenges regarding the removal of files. Techniques traditionally employed in magnetic media are not effective when applied to non-volatile memories, such as flash memory. Because of the peculiar characteristics of this type of memory, notably the existence of a Flash Translation Layer (FTL), operating systems only manage logical blocks, and no longer have direct control of the physical blocks of a flash memory. Consequently, new methods of safe removal have been developed, which employ Zero Override, Block Erase, and Cryptographic Erase techniques. This work analyzes these methods, compares their operations and proposes a new method, with better performance than those described in the literature. The proposed method is a hybrid method, which combines overwriting and deletion operations to obtain a balanced use of these operations, avoid unnecessary deletion of unused blocks and reduce premature memory wear. To verify the efficiency of the proposed method and of the other methods, a simulator was developed to exercise the removal of files in several experiments.